Review the principle of trust in the marketing of investment-linked insurance products (PAYDI) in bancassurance - Cindy Indudewi Hutomo; Agus Yudha Hernoko; Trisadini Prasastinah Usanti; Zahry Vandawati Chumaida (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Trust is an essential element in the realm of investment. This study examines two legal issues in Bancassurance's PAYDI marketing. This study employs normative legal research, a systematic scientific approach used to address legal concerns that result from regulation. The utilized data consists of secondary sources, including statutes, judicial rulings, legal doctrines, and scholarly viewpoints. This study suggests that it is important to examine the teleological contractual relationship between the parties involved, particularly those that place importance on the social and moral components of the contract's goal. The collaboration between PAYDI and life insurance firms in implementing bancassurance marketing strategies with distribution business models is essential.